Taxonomic notes on the genus Euodynerus Dalla Torre (Hymenoptera: Vespidae: Eumeninae) from Northern Vietnam - Hoa, Dang Thi; Phuong Lien, Nguyen Thi; Kojima, Jun-ichi (Academia Journal of Biology, 2013)
A taxonomic study of the genus Euodynerus Dalla Torre from Northern Vietnam is reported. The following four forms included in three species were recorded: E. dantici violaceipennis Giordani Soika, E. nipanicus nipanicus (von Schulthess), E. nipanicus tonkinensis Giordani Soika and E. trilobus (Fabricius). Of these, E. dantici violaceipennis and E. nipanicus nipanicus were newly recorded for Vietnam. Keys to species and subspecies are presented and records of their distribution in Northern Vietnam are also provided. This is the first result on the taxonomy of genus Euodynerus in Vietnam and the distribution records is an important contribution to the study on the distribution pattern of the species in genus in Asia